Services liberalization and productivity of manufacturing firms : Evidence from Ukraine - Shepotylo, Oleksandr; Vakhitov, Volodymyr (2012)
This paper brings new evidence on the impact of services liberalization on the performance of manufacturing firms. Using a unique database of Ukrainian firms in 2001-2007, the authors utilize an external push for liberalization in the services sector as a source of exogenous variation to identify the impact of services liberalization on total factor productivity (TFP) of manufacturing firms. The results indicate that a standard deviation increase in services liberalization is associated with a 9 percent increase in TFP. Allowing services liberalization to dynamically influence TFP through the investment channel leads to an even larger effect. The effect is robust to different estimation methods and to different sub-samples of the data. In particular, it is more pronounced for domestic and small firms.